KINERJA PRIMARY FAN T1 TOG PT NHM - Patrisia Pulu (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
PT NHM is a gold mining company located in North Maluku Province that uses an underground mining system. The TOG mine has a relatively high groundwater temperature due to the contact of tectonic activity in the area with meteoric water from the surface. Therefore, the level of clean air required is relatively more so that mining activities in the tunnel can run effectively. To achieve this, the supply of clean air must be balanced with the amount of dirty air released using Axial fan Howden type AFSO 1200/2450 with 560 kW/690 V motors, which are installed in parallel with a fan diameter of 2,450 mm, speed of 989 rpm with a suction capacity of 315 m3/s. The performance of the primary fan T1 TOG in PT NHM was analyzed by calculating the psychometric value of air in the fan, the value of inlet volume, resistance, air power, and efficiency values. Based on the results of data processing, there were three different conditions. The inlet volume value of the 019 fan is 170.753 m3/s, with a resistance of 0.04 Ns/m8 and an efficiency value of 81%. Meanwhile, the inlet volume value of the 018 fan is approximately 173.27 m3/s, with a resistance of 0.04 Ns/m8 and the fan efficiency value of 85%. For the conditions when both fans are operated simultaneously, the inlet volume value is 306 m3/s, with a resistance value of 0.85 Ns/m8, and the value of fan efficiency of 91%. This means that the performance of the primary fan T1 TOG in PT NHM is in good condition even though the inlet volume produced has not reached the production target according to the company's needs of 315 m3/s.